2020
DOI: 10.3389/fimmu.2020.00201
|View full text |Cite
|
Sign up to set email alerts
|

Key Components of the Complement Lectin Pathway Are Not Only Required for the Development of Inflammatory Arthritis but Also Regulate the Transcription of Factor D

Abstract: inflammatory conditions reversed this effect on FD levels. LPS is recognized by Toll-like receptor 4 (TLR4), we found MBL not only binds to TLR4 an interaction with a K d of 907 nM but also upregulated FD expression in differentiated adipocytes. We show that MASP-2 knockdown impairs the development of RA and that the interrelationship between proteins of the LP and the AP may extend to the transcriptional modulation of the FD gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, the pathway with the highest enrichment ratio (22.101) was the lectin pathway of complement activation (R-MMU-166662), which is a component of the innate immune system (Figure 32) (Ali et al, 2012). As we have seen by assessing different tissues, components of this lectin pathway of complement activation are present in all immune related tissues of the body, but are made mostly in the liver (Holers et al, 2020). The lectin pathway of complement activation is present during normal physiology in low levels to monitor for pathogens, present during sickness to recruit macrophages to the sick tissues, and present in autoimmune functions (Farrar et al, 2016).…”
Section: Network Analysesmentioning
confidence: 99%
“…Interestingly, the pathway with the highest enrichment ratio (22.101) was the lectin pathway of complement activation (R-MMU-166662), which is a component of the innate immune system (Figure 32) (Ali et al, 2012). As we have seen by assessing different tissues, components of this lectin pathway of complement activation are present in all immune related tissues of the body, but are made mostly in the liver (Holers et al, 2020). The lectin pathway of complement activation is present during normal physiology in low levels to monitor for pathogens, present during sickness to recruit macrophages to the sick tissues, and present in autoimmune functions (Farrar et al, 2016).…”
Section: Network Analysesmentioning
confidence: 99%
“…Furthermore, it was demonstrated that MASP-1 contributes to the pro-inflammatory activation of endothelial cells and increases endothelial permeability [ 82 , 83 , 84 ]. Recently, MASP-1 was reported to affect the transcription of alternative pathway factor D [ 85 ].…”
Section: Mbl-associated Serine Proteases (Masp) and Their Related mentioning
confidence: 99%
“…Moreover, it is able to activate prothrombin, and thus, participate in activation of the coagulation system (reviewed by Garred et al [ 19 ] and Pihl et al [ 20 ]) Although another MASP-2 substrate is kininogen, its cleavage does not lead to creation of bradykinin [ 16 ]. Like MASP-1, MASP-2 was recently reported to participate in the regulation of factor D transcription [ 85 ].…”
Section: Mbl-associated Serine Proteases (Masp) and Their Related mentioning
confidence: 99%
“…However, a key role of MASP-1 in MASP-2 activation was established (27). It moreover enables cross-talk with the coagulation and contact systems (28,29), contributes to activation of platelets (30), endothelial cells, affects endothelial permeability (31)(32)(33), and regulates the transcription of complement factor D (34).…”
Section: Introductionmentioning
confidence: 99%